CONTENT ANALYSIS OF INTERPRETATION OF FOREIGN LANGUAGE COMPETENCE IN PSYCHOLOGICAL AND PEDAGOGICAL LITERATURE - Ivanov, Yevhen (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
One of the important tasks of higher education today is the training of competent and competitive specialists who can effectively solve complex tasks, show flexibility and non-standard thinking, adapt to rapid changes in the modern environment. On the path of Ukraine’s integration into European economic, political and cultural and educational structures, society needs specialists who not only have high professional competence, but also possess a sufficient level of foreign language communicative competence. At the current stage, such personal competence becomes the leading goal of foreign language learning by students of higher education institutions of various fields of study, and the use of a foreign language as a means of intercultural communication and enrichment of professional training experience is the final result. The purpose of our study is the theoretical substantiation of the structure and content of foreign language communicative competence as the basis of communicative culture. A number of general scientific methods are used in the research process: analysis (comparative analysis, content analysis), synthesis, classification, comparison, etc. Based on the analysis of the psychological and pedagogical literature, as a result, we identify the essential signs and relationships between the professional and foreign language communicative competence of the future specialist, conduct a content analysis of the concepts of "competence", "competency", "competence approach", etc., systematize and classify these concepts. Most of the scientists agree that foreign language competence is a person’s ability to directly communicate in a foreign language in appropriate speech situations, taking into account language, speech and stylistic norms and rules of communicative behavior. This type of competence is considered as the readiness of the future specialist for foreign language communication. Nevertheless, certain inaccuracies were found in the translation of foreign language terms, which resulted in a number of disputes and inconsistencies. There is no universally accepted system of classification of the complex of foreign language competences due to the fact that researchers have inconsistencies in the definitions of the concepts "foreign language competence", "foreign language communicative competence", "communicative competence", etc. As a conclusion, we assume that the definition of foreign language communicative competence has not been finalized and needs more detailed research